SAT0531 Updated Eular Evidence-Based Recommendations for the Management of Gout. (10th June 2014) - Richette, P.; Doherty, M.; Pascual, E.; Barskova, V.; Becce, F.; Coyfish, M.; Janssens, H.; Jansen, T.; Lioté, F.; Mallen, C.; Nuki, G.; Perez-Ruiz, F.; et al.
Abstract : Background: Despite its high prevalence and availability of effective treatments, recent reports have shown that gout is often poorly managed. New drugs and new evidence concerning the use of established treatments have become available since publication of the first EULAR recommendations in 2006. This has prompted a systematic review and update of the 2006 recommendations. Objectives: To develop updated evidence based recommendations for the management of gout. Methods: The 2014 EULAR task force comprised 15 rheumatologists, 1 radiologist, 2 GPs, 2 patients and 2 experts in methodology. The expert group first voted to determine whether each 2006 recommendations for management should be retained, modified or deleted. MEDLINE, EMBASE and Cochrane Library reports were searched to obtain research evidence from 2005 to 2013 on all aspects of the management of gout. The quality of evidence was categorised according to GRADE. The task force was presented with a summary of this literature review and generated a first draft of key recommendations after a two-day meeting. Final recommendations were agreed using a Delphi consensus approach. Results: Fourteen key recommendations were generated, including core principles for the patient management such as education and assessment for comorbidities. Urate-lowering therapy (ULT) should be considered from the first presentation of disease and serum urate (SUA) levels should be maintained below 6 mg/dl in every patient, and below 5 mg/dL in patients with severe gout. Allopurinol is recommended as first line ULT in patients with normal renal function. If the SUA target cannot be achieved with an appropriate dose of allopurinol, febuxostat, a uricosuric, or a combination of a xanthine oxidase inhibitor with a uricosuric should be substituted. In patients with severe gout and poor quality of life, in whom the SUA target cannot be reached with any other therapeutic option, pegloticase is indicated. For the treatment of acute flares, colchicine, NSAIDs, oral or intra articular steroids are recommended, the choice being determined by the presence of contraindications, patient's previous experience of treatments, time of initiation after flare onset, and the number and location of joint(s) involved. In frequently flaring patients who were contra-indicated for colchicine, NSAIDs and corticosteroid, IL-1 blockers should be considered. Prophylaxis against flares should be fully explained and discussed with the patients. Other recommendations include advice for managing patients with renal failure. Conclusions: Fourteen updated, evidence-based, expert recommendations for the management of gout are proposed. Disclosure of Interest: P. Richette Speakers bureau: Ménarini, Ipsen, Savient, Novartis, Astra-Zeneca, M. Doherty Speakers bureau: Menarini, Ardea and Novartis, E. Pascual Speakers bureau: Menarini, Savient, Novartis, Astra Zaneca, V. Barskova: None declared, F. Becce: None declared, M. Coyfish: None declared, H. Janssens: None declared, T. Jansen Speakers bureau: Ménarini, F. Lioté Speakers bureau: Novartis, Ipsen, Menarini, SOBI, Mayolly-Spindler, Astra-Zeneca, Ardea, Savient, C. Mallen: None declared, G. Nuki Speakers bureau: Ipsen, Menarini, Novartis and Savient., F. Perez-Ruiz Speakers bureau: Astra-Zeneca, Menarini, Metabolex, Novartis, Pfizer, SOBI, J. Pimentão Speakers bureau: Ménarini, T. Piwell: None declared, L. Punzi Speakers bureau: Ménarini, A. So Speakers bureau: Novartis, SOBI, Astra-Zeneca and Menarini, A.-K. Tausche Speakers bureau: Menarini, Savient, Novartis, Sobi, Ardea Bioscience, T. Uhlig: None declared, J. Zavada Speakers bureau: Ménarini, Novartis, W. Zhang Speakers bureau: Savient, F. Tubach: None declared, T. Bardin Speakers bureau: Ménarini, Ipsen, Savient, Novartis, Astra-Zeneca, SOBI DOI: 10.1136/annrheumdis-2014-eular.5022